Offenses Against Public Safety, Chapter 6, § 387 - (:unkn) unknown (General Publisher, 1885)
Prohibited keeping more than twenty-five pounds of gun powder or other explosive. Also prohibited sale of gun powder by artifical light.
--
Keywords: GUN POWDER STORAGE